IMPACT OF ANESTHESIA ON BLOOD PRESSURE CONTROL IN HYPERTENSIVE PATIENTS DURING GENERAL SURGERY.: JPUMHS;2024:14:04,145-151. http://doi.org/10.46536/jpumhs/2024/14.04.572 - Mobasher Ahmad Saeed1, Jamshed Bashir2, Khurram Liaqat3, Khushal Khan4, Mashooque Ali5, Sadia Ayoob6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Hypertension is a significant risk factor for increased mortality during anesthesia. Withdrawal from antihypertensive medications can lead to complications like anxiety, rebound hypertension, myocardial infarction, and death. OBJECTIVE: This study aimed to evaluate the effects of anesthesia on perioperative blood pressure management in hypertensive patients undergoing general surgeries. METHODOLOGY: A prospective observational study was conducted at federal government Polyclinic hospital PGMI, from April 2023 to March 2024. Seventy hypertensive patients aged 40–65 years undergoing elective general surgery under general anesthesia were included. BP was measured preoperatively, intraoperatively, and postoperatively, with fluctuations recorded. Key factors observed included blood loss, anesthesia drugs, haemodynamics heart rate, systolic and diastolic blood pressure, antihypertensive medication use, and fluid consumption. SPSS version 27 was used for data analysis. RESULTS: The mean patient age was 56.4 ± 8.7 years, with 65% males. Pre-induction SBP was 145.9 ± 10.6 mmHg and DBP 90.5 ± 7.3 mmHg. Intraoperative BP dropped significantly, with a mean SBP decrease of 18.5 mmHg p < 0.01. Hypotension occurred in 35% of patients, requiring vasopressors, while 12% experienced hypertension. Postoperative BP stabilized in 65% of patients. Beta blocker use was significantly associated with lower postoperative heart rates p = 0.034, while diuretics showed a trend toward lower heart rates but did not reach significance. CONCLUSION: General anesthesia led to significant BP fluctuations in hypertensive patients, with 35% experiencing hypotension. Beta blocker use was effective in controlling postoperative heart rate.